Survey of People with Mental Disorders in Waingapu City District, East Sumba District, 2017 - Agustine, Uly; Karahanau, Marwin U.K. (Poltekkes Kemenkes Kupang, 2018)
Background:The problem of mental disorders throughout the world has become a very serious problem. WHO states there are at least 1 in 4 people in the world experiencing mental problems, it is estimated there are around 450 million people in the world who experience mental health disorders. The aim is to identify people with mental disorders based on: Demographics include: age, sex, education and employment and Nursing Diagnosis includes: violent behavior, social isolation, low self-esteem, hallucinations and self-care deficits in Kota Waingapu District, East Sumba Regency. Methods: This type of research uses descriptive. The sampling technique is total sampling. Results: From the results of the study found from 30 respondents the distribution of male sex suffered the most mental disorders as many as 16 people (53.3%), the age distribution that suffered the most from mental disorders aged 26-35 were 11 people (36.7%) , Education distribution that suffered the most from mental disorders with elementary school education was 14 people (46.7%) and the distribution of jobs that suffered the most from mental disorders by not working was 28 people (93.3%) and based on the most nursing diagnoses who experienced disorders hallucinations as many as 12 people (40%), Violence Behavior as many as 12 people (40%). Conclusion: With the presence of patients with mental disorders, it is expected that more patients will be considered in terms of treatment and health service agencies apply soul programs, especially in the government of East Sumba district.